A Possible Tool for Guiding Therapeutic Approaches to Urinary Infections with Klebsiella pneumoniae: Analyzing a Dataset from a Romanian Tertiary Hospital - Dragos Stefan Lazar; Maria Nica; Daniel Romeo Codreanu; Alma Gabriela Kosa; Lucian L. Visinescu; Corneliu Petru Popescu; Ion Cristian Efrem; Simin Aysel Florescu; George Sebastian Gherlan (Antibiotics)
Introduction: The emergence of carbapenem-resistant pathogenic bacteria is a growing global public health concern. Carbapenem-resistant uropathogenic strains of Klebsiella pneumoniae can cause uncomplicated or complicated urinary tract infections, leading to a high risk of treatment failure and the spread of resistance determinants. The objectives of this 24-month study were to identify the prognostic characteristics of patients who were infected with carbapenem-resistant Klebsiella pneumoniae (CRKpn) and to create a tool to estimate the probability of a CRKpn infection before having the complete results of a patient’s antibiogram. Results: We found that 41.6% of all urinary infections with Kpn were caused by CRKpn. Factors such as male gender, the presence of upper urinary tract infections, invasive urinary maneuvers, recent infection with or carriage of the germ, and the nosocomial occurrence of UTIs with Kpn were predictive for CRKpn infection. Based on these factors, we proposed a model to estimate the presence of CRKpn. Methods: A retrospective case–control study including all hospitalized patients with urinary tract infections (UTIs) caused by Klebsiella pneumoniae was carried out. We reported data as percentages, identified independent predictors of the presence of CRKpn, and proposed a tool to evaluate the probability through multivariate analysis. Conclusions: Through this study, we aim to provide clinicians with a tool to support decision making regarding first-line antibiotic treatment.